2009
DOI: 10.1261/rna.1749109
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis RNase J1 endonuclease and 5′ exonuclease activities in the turnover of ΔermC mRNA

Abstract: RNase J1, a ribonuclease with 59 exonuclease and endonuclease activities, is an important factor in Bacillus subtilis mRNA decay. A model for RNase J1 endonuclease activity in mRNA turnover has RNase J1 binding to the 59 end and tracking to a target site downstream, where it makes a decay-initiating cleavage. The upstream fragment from this cleavage is degraded by 39 exonucleases; the downstream fragment is degraded by RNase J1 59 exonuclease activity. Previously, DermC mRNA was used to show 59-end dependence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…This does not rule out the possibility that alternative endonucleasedependent pathways exist for the turnover of at least some portion of these mRNAs, as suggested recently for ∆ermC. 23 Endonucleolytic cleavage by RNase J1. There are a number of clearer examples of a role for RNase J1 endonucleolytic activity in RNA processing and decay.…”
Section: Role Of Rnase J1/j2 In the Turnover Of Specific Rnasmentioning
confidence: 85%
See 1 more Smart Citation
“…This does not rule out the possibility that alternative endonucleasedependent pathways exist for the turnover of at least some portion of these mRNAs, as suggested recently for ∆ermC. 23 Endonucleolytic cleavage by RNase J1. There are a number of clearer examples of a role for RNase J1 endonucleolytic activity in RNA processing and decay.…”
Section: Role Of Rnase J1/j2 In the Turnover Of Specific Rnasmentioning
confidence: 85%
“…However, a model of ribosome-dependent endonucleolytic cleavage by RNase J1 at the upstream boundary of the stalled ribosome is favored by the authors for both ∆ermC and lac-rpsO. 20,22,23 It is not immediately clear to me, however, why these mRNAs would be any different to the cryIIIA and hbs mRNAs. Since the generation of the ribosome-protected species is inhibited by the addition of secondary structures to the 5' end of the ∆ermC and lac-rpsO transcripts, this was interpreted as evidence that the endonucleolytic cleavage by RNase J1 is 5'-end dependent, with the enzyme scanning to the site of ribosome-dependent cutting.…”
Section: Role Of Rnase J1/j2 In the Turnover Of Specific Rnasmentioning
confidence: 99%
“…It has been implicated in the trimming of 16S rRNA (Britton et al 2007;Mathy et al 2007), and the turnover of small RNAs such as the trp and thrS leaders and DermC (Even et al 2005;Deikus et al 2008;Yao et al 2009). There is also evidence that RNase J has a broader role in determining mRNA lifetime (Mader et al 2008;Bugrysheva and Scott 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For several mRNAs studied (ermC, rpsO, cryIIIA, hbs), the generation of shorter, often more stable mRNA transcripts is thought to be due to RNase J1 exonuclease activity, which trims a longer precursor before it is partially halted, generally by a bound or stalled ribosome (18,(87)(88)(89)(90). In some cases (ermC, rpsO), it has been suggested that RNase J1 might act as an endonuclease, but the corresponding upstream RNA fragments have never been detected (91).…”
Section: Mrna Turnover: Endo-versus Exonucleolytic Activitymentioning
confidence: 99%